What affects publications' popularity on Twitter? - Zhang, Liwei (2022)
Social media is one of the major channels for knowledge diffusion, including scientific discovery. As a consequence, it has been under discussion whether altmetrics can be used as an alternative indicator for research evaluation, complementing the traditional indicators such as citations. The study contributes to the discussion by exploring the factors relevant to the attention that publications receive on social media. Based on 20,310 academic papers published by the Royal Society in the past ten years, the study found that posting accounts are the major force for boosting the amount of attention received on Twitter. Timely posting and accessibility also help to increase the attention. The findings suggest that publications’ social popularity can be easily influenced by non-paper factors.